IMPROVING READING COMPREHENSION THROUGH ACTIVATING STUDENTS’ SCHEMATA (A Classroom Action Research at Dian Nuswantoro University Semarang in the Academic Year of 2011-2012) - Liya Umaroh (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2015)
This research investigated the improvement of reading comprehension through activating students’ schemata. It was carried out on the first semester at Dian Nuswantoro University Semarang in the academic year 2011/2012. During the process of observation phase, some problems found in reading classroom activities, those are: most of students felt unmotivated in reading class, got bored, were confused to understand the content of the text, had less willingness, had limited number of vocabulary, had bad score in English subject from their UAN, and also had bad score from their English Subject when they were tested before entering the university. The first goal of this research is to discover the problems when ActivatingSchemata strategy implemented, the second goal is to describe the situation on the strategy applied, the third goal is to measure how far the improvement of students’ reading comprehension during Activating Schemata strategy implemented. Classroom Action Research used in the research as a research methodology that classified into planning activity, acting, observing and reflecting. There were three cycles used in the research. The research findings showed that reading comprehension improved through Activating Schemata. It can be seen from the students’ behavioral changes, such as: 1) they got easier to activate their schemata, 2) they got easier to do reading exercises, and 3) they realized that reading subject is intersting. The improvement also showed in their average score (60.33) pre test score, (66.25) test one, (71.42) test two, (77.33) post test score. This implied that students’ reading comprehension improved through Activating students’ Schemata.Keywords : activating schemata, classroom action research, reading comprehension.